Chronic liver disease and management with silymarin: an introductory review of a clinical case collection - Francesco Angelico (BioExcel Publishing Ltd, 2024)
Chronic liver disease (CLD) is a significant global health concern and generally leads to fibrosis, cirrhosis and hepatocellular carcinoma. Various factors, such as metabolic abnormalities, viral infections, alcoholism, genetics and autoimmune responses, contribute to liver damage. CLD is characterized by different phenotypes, including non-alcoholic fatty liver disease, metabolic-associated fatty liver disease, drug-induced liver injury and alcoholic liver disease. These conditions have seen an increase in comorbidities and hospitalizations over the past decade, imposing a substantial burden on patients and healthcare systems. Understanding the underlying mechanisms of liver injury is crucial for effective management and reducing the clinical and economic burden of CLD. Although several attempts have been evaluated to find a drug therapy option for the management of non-alcoholic fatty liver disease and metabolic-associated fatty liver disease, there is no effective drug approved to date. However, different studies have demonstrated that silymarin, the milk thistle extract, could exert hepatoprotective, antioxidant, anti-inflammatory and antifibrotic properties and should therefore be considered an efficacious, tolerable and promising herbal product for the management of liver activity in CLDs. This review discusses the clinical features, diagnosis and available treatments for major liver diseases, acting as an introduction to a clinical case collection based on the management and treatment of major liver diseases with silymarin. This article is part of the Current clinical use of silymarin in the treatment of toxic liver diseases: a case series Special Issue: https://www.drugsincontext.com/special_issues/current-clinical-use-of-silymarin-in-the-treatment-of-toxic-liver-diseases-a-case-series